Behavioral Segmentation of Baby Food Consumers: Risk Areas, Possible Solutions. The Case of Ukraine - Shashkova, Nina; Ushkarenko, Iuliia; Soloviov, Andrii; Osadchyi, Oleksii; Nitsenko, Vitalii (European Journal of Sustainable Development, 2021)
The concept of this work is based on the idea of the interrelation of socio-demographic factors and factors of enterprises strategic development (baby food producers). According to the key indicators, the main components identify the psychographic characteristics of baby food consumers. Each factor included features with the highest factor load after geometric rotation by the Varimax method. The most critical areas of social status, stereotypical representation, consumer standards are found, which signal urgent problems that can be solved only if efforts of public and private solutions are combined (Foresight design). Social PR projects are a possible solution for a long-term program to expand the domestic market for baby food. The mechanism of implementation is to provide an opportunity for enterprises producing baby food products to participate in the implementation of national and regional programs to support fertility and family policy in Ukraine. It is suggested to introduce the results of marketing analysis of psychographic segmentation of consumers of baby food products into Foresight-design programs. The study proposes to integrate the marketing communication policy of baby food manufacturers and government policies in the field of fertility support in Ukraine, based on the principles of Foresight engineering for the social projects implementation.